Poland’s Trade in Services with Germany – EU Membership Experience - Kuźnar, Andżelika (Zeszyty Naukowe SGGW w Warszawie - Problemy Rolnictwa Światowego, 2016)
Services play an increasingly important role in economies and international trade and are a vital element of building competitive advantage of nations. The aim of the paper is to determine the competitive position of Poland in trade in services with Germany and its changes. The RCA index is used to determine the international competitiveness of services. A special attention is devoted to high-tech knowledge-intensive services due to their potential impact on building competitiveness of all sectors of economy. Germany is a reference country as it is the most important trade partner of Poland. The time scope covers generally years 2004-2014. The analysis revealed that services development is lagged in Poland in comparison with Germany, but there is an ongoing convergence of structures of both economies. The share of high-tech services increased in Poland’s services exports, but Poland does not reveal comparative advantage in any of high-tech knowledge-intensive services.